Servant Leadership on Work Engagement: Mediating Job Satisfaction and Trust in Leader - Putri, Haliza Nabila; Daud, Ilzar; Rosnani, Titik; Fahruna, Yulyanti; Shalahuddin, Ahmad (Jurnal Informatika Ekonomi Bisnis, 2023)
The banking industry is currently one of the most competitive industries. For this reason, a leadership style is needed that can increase employee engagement to achieve better company performance. The aim of this research is to ascertain the impact of servant leadership workers' job satisfaction and trust in their leaders as mediating variables. It is conducted at government-owned banks, namely, Bank BNI, Bank BRI, Bank BTN, and Bank Mandiri. Purposive sampling was the technique employed in this study, and the sample consisted of 273 individuals who worked for government-owned banks. This study employed structural equation modeling (SEM) with AMOS software as a data analysis technique. The study's findings demonstrate that: servant leadership influences job satisfaction significantly; job satisfaction influences work engagement significantly; Trust in Leader significantly influences work engagement; job satisfaction mediates the relationship between servant leadership and work engagement; and Trust in Leader mediates the relationship between servant leadership and work engagement. There is one rejected hypothesis, namely, that employee engagement at work is not significantly impacted by servant leadership.